Energy efficient automotive networks: state of the art and challenges ahead. (1st January 2012) - Schmutzler, Christoph; Krüger, Andreas; Schuster, Fred; Simons, Martin
Rising fuel prices, challenging emission standards and the introduction of electric powertrains lead car manufacturers to explore every possible way to design energy efficient vehicles. Apart from increasing powertrain efficiency, e.g., by downsizing and optimising mechanical components as well as primary aggregates, the development of energy efficient Electric/Electronic-architectures will also contribute towards this goal. However, current architectures support none or only rudimentary power saving mechanisms. Furthermore, system design decisions made in the past such as broadly implementing a cyclic communication paradigm prevent the implementation of simple and straightforward power saving strategies. This paper surveys current in-vehicle Electric/Electronic-architectures and their energy efficiency and outlines new hardware and software approaches that allow for an easy and backwards compatible migration strategy.